(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract In order to implement the On-the-Job program for the Bachelor of Library and Information Science at Bestlink College of the Philippines, the study sought to identify the difficulties encountered by student trainees and practicum coordinators. The study involved the formulation of guiding questions and the selection of 30 fourth-year BLIS students through purposive sampling. Library Science programs often require students to complete internships, which can provide valuable real-world experience. Developing an internship program could benefit both the library and the student. A survey questionaire sent via Google Mail was used to collect data. Percentages and weighted mean were used to analyze the data that had been gathered. Student interns can help teachers and students by choosing books and other resources, promoting more reading, and enhancing vocabulary, general knowledge, and important concepts. Internships in libraries give students the chance to gain practical experience while also learning from seasoned librarians. The emphasis of these internships should be on education and learning. Regular updates to the Library and Information Science (LIS) curriculum are necessary to meet the evolving needs of LIS practitioners. There is often a gap between theory and practice in LIS, and inadequate resources such as computer laboratories and libraries limit students’ hands-on experience. On-the-job training (OJT) is necessary to prepare students for the workforce and provide orientation, benefits, and motivation. This study evaluated the role of OJT in improving the knowledge of BLIS students at Bestlink College of the Philippines.